2019
DOI: 10.1523/eneuro.0444-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

MVPA Analysis of Intertrial Phase Coherence of Neuromagnetic Responses to Words Reliably Classifies Multiple Levels of Language Processing in the Brain

Abstract: Neural processing of language is still among the most poorly understood functions of the human brain, whereas a need to objectively assess the neurocognitive status of the language function in a participant-friendly and noninvasive fashion arises in various situations. Here, we propose a solution for this based on a short task-free recording of MEG responses to a set of spoken linguistic contrasts. We used spoken stimuli that diverged lexically (words/pseudowords), semantically (action-related/abstract), or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
3
8
0
Order By: Relevance
“…We then proceeded to classify these contrasts in each of the five pre-defined frequency bands for both the young and the older group. We could, in line with previous research (M. Jensen et al, 2019), classify the different language processes, and found different time courses across the frequency bands. Crucially, the classification features differed not only between the bands and linguistic contrasts but also between the age groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We then proceeded to classify these contrasts in each of the five pre-defined frequency bands for both the young and the older group. We could, in line with previous research (M. Jensen et al, 2019), classify the different language processes, and found different time courses across the frequency bands. Crucially, the classification features differed not only between the bands and linguistic contrasts but also between the age groups.…”
Section: Discussionsupporting
confidence: 91%
“…While the young group's decoding patterns were mostly expressed in the β band, the patterns for the older group were expressed in the α range instead. The finding of semantic activity in the β band for action verbs in the young group is in line with previously reported findings for word processing in general (Bastiaansen & Hagoort, 2006;M. Jensen et al, 2019).…”
Section: Semantic Conditionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, this approach ensured that the results can be more plausibly attributed to language processing per se than to any general differences that are likely to emerge with a whole-brain approach. Nevertheless, as restricting the analysis to pre-defined ROIs inherently limits the space for establishing connections, we emphasise the necessity of further investigations using less restricted (e.g., whole-brain) analysis, which may potentially also be expanded to include oscillatory measures in different frequency bands ( Jensen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…EEG MEG High pass cut-off (Hz) Low pass cut-off (Hz) (Alizadeh, Jamalabadi, Schonauer, Leibold, & Gais, 2017) • 0.1 40 (Bae & Luck, 2018) • 0.1 80 (Bae & Luck, 2019) • 0.1 80 (Barragan-Jason, Cauchoix, & Barbeau, 2015) • 0.1 40 (Blom et al, 2020) • -- (Borst, Ghuman, & Anderson, 2016) • 0.5 50 (Borst, Schneider, Walsh, & Anderson, 2013) • 0.5 30 (Brandman, Avancini, Leticevscaia, & Peelen, 2020) • 0.1 330 (Brandmeyer, Farquhar, McQueen, & Desain, 2013) • 1 25 (Carlson, Hogendoorn, Kanai, Mesik, & Turret, 2011) • -- (Carlson, Tovar, Alink, & Kriegeskorte, 2013) • 0.1 200 (Cauchoix, Barragan-Jason, Serre, & Barbeau, 2014) 0.1 40 (Chan, Halgren, Marinkovic, & Cash, 2011) • • 0.1 200 (Cichy & Pantazis, 2017) • • 0.03 300 (Cichy, Pantazis, & Oliva, 2014) • 0.03 330 (Cichy, Ramirez, & Pantazis, 2015) • 0.03 330 (Clarke, Devereux, Randall, & Tyler, 2015) • 0.03 40 (Correia, Jansma, Hausfeld, Kikkert, & Bonte, 2015) • 0.1 100 (Dash, Ferrari, & Wang, 2020) • -250 (Fahrenfort, Grubert, Olivers, & Eimer, 2017) • 0.1 - (Fahrenfort, van Leeuwen, et al, 2017) • 0.1 - (Giari, Leonardelli, Tao, Machado, & Fairhall, 2020) • 0.8 80 (Herrmann, Maess, Kalberlah, Haynes, & Friederici, 2012) • 2 10 (Hogendoorn & Burkitt, 2018) • -- (Hogendoorn, Verstraten, & Cavanagh, 2015) • -- (Hubbard, Kikumoto, & Mayr, 2019) • 0.01 80 (Isik, Meyers, Leibo, & Poggio, 2014) • 2 100 (Jach, Feuerriegel, & Smillie, 2020) • 0.5 30 (Jensen, Hyder, & Shtyrov, 2019) • 1 95 (Kaiser, Azzalini, & Peelen, 2016) • 1 330 (Kaiser, Oosterhof, & Peelen, 2016) • 1 300 (King, Pescetelli, &...…”
Section: Publicationmentioning
confidence: 99%